AUTHENTIC MATERIAL ORIENTED TASKS IN ENGLISH TEXTBOOKS - sumadi sumadi; Taniya Taniya (IAIN Syekh Nurjati Cirebon, 2020)
this research aims to explore authentic material oriented tasks in the two selected textbooks for 10th grade of Senior High School in Indonesia. The is qualitative research using the document analysis. The data were collected from two textbooks, i.e.,